Development and Validation of a Questionnaire to Assess Students’ Perception of Hyflex Learning Modality - Edrian Peter Villanueva; Jayson Caalim (Recoletos Multidisciplinary Research Journal)
The HyFlex learning modality, a response to the need for inclusive and high-quality education, has introduced significant transformations in some aspects of the Philippine education system. With students being the primary beneficiaries, understanding their perspectives on the HyFlex is crucial for its effective implementation. This research aims to create and assess the reliability and validity of a questionnaire in gauging students' experiences in a HyFlex environment. Results from early surveys and focus-group discussions have generated a 25-item questionnaire. The researchers have administered the questionnaire to 460 students in the HyFlex environment using Microsoft Forms. Exploratory factor analysis has reduced the items to 23 and generated four factors: interpreted as perceived teacher support, utilization of HyFlex, learning engagement, and learning efficacy. These factors explain 55.1% of the variance. Confirmatory factor analysis and reliability analyses confirm the questionnaire's validity and reliability. Results from the initial questionnaire application suggest that students generally perceive HyFlex positively.